Revisiting the environmental Kuznets curve hypothesis: measuring the effect of international environmental treaties on the relationship between GDP and environmental quality - Chung, Jang Hoon; Lah, T.J. (International review of public administration, 2014)
This study explores the effects of international environmental cooperation that enhances a country's environmental quality. The authors analyzed the impact of participation in international environmental cooperation on the environmental Kuznets curve through Generalized Least Squares estimation of the two-way fixed-effects model. Data are organized in the form of a pooled time series in which information is collected annually on 148 nation-states from 1997 to 2011. Our hypothesis tested whether participating in international environmental cooperation would increase the effect of economic development on environmental improvement. The analysis confirmed that prior to reaching the environmental turning point, participation in international environmental cooperation improves environmental quality. However, international environmental cooperation had no effects after achieving a certain level of economic development. The paper argues that this is due to the flexible nature of international environmental cooperation.